Reactions using whole cell biocalytic lens culinaris (lentil) - Daniele Alves Ferreira (2012)
This paper describes the use of seeds of lentil (Lens culinaris) as intact plant system in biocatalytic reactions of reduction and hydrolysis. Initially, some plant sources were evaluated for their action in the biocatalytic reduction of aromatic ketone acetophenone. The plants that showed positive results in the reduction reaction underwent determination of their protein content by the methods of Lowry and Bradford. Lens culinaris was plant species revealed that most relevant biocatalytic activity, in agreement with their high protein content (1.33 mg / mL and 1.07 mg / mL according to Bradford and Lowry methods, respectively), and thus The plant was selected for further study. Subsequently, always using the model substrate acetophenone as the reaction parameters were optimized: concentration of biocatalyst; reaction kinetics; stirring speed the reaction medium. After selecting these parameters, the bioreduction reactions were extended to other derivatives of prochiral acetophenone, which were observed with bioconversions yields and enantiomeric excess (ee) ranging from low to high percentages. Generally, were observed steric and electronic influences due to the type and relative position of the various substituents on aromatic compounds. In the case of substrates containing two different functional groups susceptible to reduction, low chemoselectivity observed. Investigated also other carbonyl compounds such as aliphatic and aromatic ketones, aromatic aldehydes and aromatic nitro compounds. In addition investigated the possibility that hydrolytic action from compounds belonging functions esters, amides and nitriles. The yields of the reactions were calculated using Gas Chromatography coupled with Mass Spectrometry (GC-MS) and Nuclear Magnetic Resonance Hydrogen (1H NMR). The enantiomeric excess (ee) were determined by High Performance Liquid Chromatography (HPLC) equipped with chiral columns.